Pediatric Palliative Care: A Quality Improvement Recommendation - Williams, Melinda L. (My University, 2015)
In the United States, there are greater than 500,000 infants and children living with a life-threatening or life-limiting condition. Advances in healthcare allow children with life threatening or life limiting conditions to live longer than they have in the past. However, each year at least 55,000 children die, with approximately eighty percent of these deaths occurring in hospital setting. According to the American Academy of Pediatrics, children with life threatening or life-limiting illnesses should have access to competent, compassionate, and developmentally appropriate palliative care that is initiated at time of diagnosis. Pediatric palliative care is a relatively new discipline with limited research and specialized training consequently, not all healthcare institutions have a dedicated program. This author’s project focused on a quality improvement initiative that utilized a formal organizational review to identify a need for pediatric palliative care services followed by synthesis and dissemination of the findings to encourage the development of an inpatient pediatric palliative care program.
Keywords: Pediatric Palliative Care